2013
DOI: 10.1902/jop.2012.120378
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss and Periodontitis in Older Individuals: Results From the Swedish National Study on Aging and Care

Abstract: The prevalence of periodontitis increased with age. Sex seems to be the dominant explanatory factor for periodontitis in older individuals. Despite frequent dental visits, overall oral health in the oldest age cohort was poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 49 publications
8
64
0
3
Order By: Relevance
“…Loss of teeth progresses during the course of life [3,4] due to the destruction of teeth by caries, disease and the loss of tooth supporting tissues due to periodontal disease. Gradual tooth loss causes successive reduction in chewing ability.…”
mentioning
confidence: 99%
“…Loss of teeth progresses during the course of life [3,4] due to the destruction of teeth by caries, disease and the loss of tooth supporting tissues due to periodontal disease. Gradual tooth loss causes successive reduction in chewing ability.…”
mentioning
confidence: 99%
“…However, tooth loss due to aging is not inevitable; i.e., tooth loss is not a normal phenomenon in elderly individuals, although many studies have reported that tooth loss is an outcome of aging and that age is an indicator of tooth loss. 22,23 Age alone cannot be used to predict the number of present teeth. In this prospective cohort study, we found that the number of present teeth in middleaged/elderly participants was associated with tooth retention at an older age, even after adjusting for sociodemographic status and oral health behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The number of present teeth is associated with age and is an important indicator of oral health; 22,23 however, it is difficult to estimate the number of present teeth on the basis of age alone. A previous study reported that the number of present teeth in individuals at the ages of 50-59 years and 56-65 years was associated with tooth loss 6 years later.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal disease (PD) is characterized by the destruction of connective tissue and alveolar bone after an inflammatory response of the host to infection by pathogens that can lead to tooth loss, affecting more than 80% of the population worldwide. Its multifactorial etiologic character includes different risk factors such as obesity and osteoporosis, which can contribute to its emergence and prevalence [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%